PENGARUH AKTIVITAS BERMAIN KELOMPOK KOOPERATIF TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK KELOMPOK B DI TK DOREMI REMBIGA - Ingesti Pangestuti; M.A Muazar Habibi; Filsa Era Sativa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effect of cooperative group play activities on the social-emotional development of Group B children at TK Doremi Rembiga. The research employed a quantitative approach using a pre-experimental method with a One Group Pretest–Posttest Design. The participants consisted of 15 Group B children selected through a total sampling technique. Data were collected using an observation instrument comprising 30 indicators of social-emotional development. The data were analyzed using descriptive statistics and inferential analysis through the Paired Sample t-Test at a 5% significance level. The results indicated that the mean score of children's social-emotional development increased from 88.60 in the pretest to 92.00 in the posttest. The percentage of social-emotional development also increased from 73.83% to 76.67%. Furthermore, the hypothesis testing showed that the calculated t-value (4.328) was higher than the t-table value (2.145), indicating that the alternative hypothesis was accepted. These findings demonstrate that cooperative group play activities have a significant positive effect on children's social-emotional development. Cooperative play provides opportunities for children to cooperate, communicate, share, develop empathy, and regulate their emotions through interaction with peers. Therefore, cooperative group play can be considered an effective learning strategy to enhance the social-emotional development of early childhood.